Shopping drivers of generational cohorts: a comparison between night market and wet market formats for fresh fruit and vegetable purchase in Malaysia - Gindi, Abdullahi Auwal; Abdullah, Amin Mahir; Ismail, Mohd Mansor; Mohd Nawi, Nolila (Elsevier, 2016)
The objective of this study is to determine the shopping drivers that influence consumers to choose the night market or wet market for fresh fruit and vegetable (FFV) purchases. The study also investigates whether any differences in behavior among generational cohorts exist while purchasing fresh fruits and vegetables between two retail formats. The cluster sampling technique was applied to the entire population of Klang Valley area in Malaysia, and 700 respondents were randomly selected for this research. Perceived freshness, perceived quality and perceived safety of the fresh fruits and vegetables are the most important shopping drivers in a consumer's decision to purchase FFV in night market and wet market retail formats. The findings show that members of different generational cohorts have different perceptions about freshness, quality and safety of fresh fruits and vegetables purchased in night market and wet market retail formats.